Export variety, productivity, and country size in a multi-good Ricardian model of export diversification - Andrzej Cieślik; Aleksandra Parteka (Gdańsk University of Technology, Faculty of Management and Economics, 2018)
This paper addresses the lack of connection between theory and empirics in most export diversification - economic development studies. We provide a Ricardian-based theoretical explanation of countries' relative export variety as a function of the level of technology and country size assessed with respect to the rest of the world. Relative export diversification is an outcome of two forces: a relative productivity change (technological progress) and a relative country size change (labour force growth). The model predictions are confirmed in a sample of 132 countries (1988-2014), including 53 low-income countries, for which we measure export variety using product-level trade data. The influence of technology differences on export variety is: (i) stronger than is the effect of cross-country differences in size and (ii) non-linear, driving diversification at the beginning of the development process. The results are robust to the measurement of export variety, the inclusion of control variables, and estimation methods.
Keywords: F11; F14; F43; O40; O11; 330; export variety; export diversification; Ricardian model; economic development